Scrutinize the United Nations Convention against Corruption (UNCAC) - Kitjapat Kesiranon (Journal of Contemporary Sociological Issues, 2023)
Corruption has been dramatically undermining human rights, and there are some legal problems in the anti-corruption law regime. This reality is not only unlawful but also naturally unfair. Therefore, using historical comparative analyses, the article aims to demonstrate two problematic issues remaining in the United Nations Convention against Corruption (UNCAC), which leave the threshold for human rights abuse and the smooth way to sustainable development, namely the absence of a precise definition of corruption and the absence of sanction provisions under the UNCAC. The article indicates the human rights undermining characteristic of corruption, the UNCAC's problems in coping with systematic corruption, which significantly violates human rights, and relevant scholarly doctrines supportive of the definability of corruption, especially the human-rights-based approach. The paper finally offers the standard definition of corruption under the Human-Rights Based Approach to cover systematic corruption that is sometimes lawful under domestic laws. Furthermore, this paper offers the systematic concrete sanction to make the Convention truly enforceable worldwide. In this regard, the roles of the International Criminal Court (ICC) should be taken into account to achieve a corruption-free society and sustainable development for humanity. Keywords: Systematic corruption, UNCAC, human rights